1999
DOI: 10.1093/humrep/14.2.458
|View full text |Cite
|
Sign up to set email alerts
|

Development of in-vitro-derived bovine embryos cultured in 5% CO2 in air or in 5% O2, 5% CO2 and 90% N2

Abstract: To evaluate the effects of a three gas mixture of 5% O2, 5% CO2 and 90% N2 (OCN) on preimplantation embryo development, bovine in-vitro fertilization (IVF) oocytes were cultured in a defined medium (mBECM) with various supplements either under 5% CO2 in air or under OCN. When cultured in mBECM alone, embryo development was significantly stimulated in OCN compared to 5% CO2 in air (experiment 1). In the OCN atmosphere, blastocyst formation was further increased after addition of fetal bovine serum (FBS; 10%) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 47 publications
2
27
0
1
Order By: Relevance
“…Embryo culture at 5% O2 has shown to produce more blastocysts per cycle with higher mean cell numbers compared to 20% O2, where significantly more blastocysts had abnormally lower cell number (<25) [30]. An efficient development to the blastocyst stage has been achieved for human [31] and bovine [32] embryos using a culture protocol of reduced O2 (5%). Subsequent studies [33,34] have confirmed that blastocysts consume two to four times more O2 than cleavage stage embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo culture at 5% O2 has shown to produce more blastocysts per cycle with higher mean cell numbers compared to 20% O2, where significantly more blastocysts had abnormally lower cell number (<25) [30]. An efficient development to the blastocyst stage has been achieved for human [31] and bovine [32] embryos using a culture protocol of reduced O2 (5%). Subsequent studies [33,34] have confirmed that blastocysts consume two to four times more O2 than cleavage stage embryos.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro culture of preimplantation embryos under various O 2 concentrations has been carried out in several mammalian species, including mice [8,9], sheep [10], cattle [11][12][13], and humans [14], and reduction of the O2 concentration from 20% to 5% during in vitro culture has been shown to enhance the development to the blastocyst stage. On the other hand, it was reported that there was no significant difference in the in vitro developmental rates to the blastocyst stage of porcine in vivo fertilized embryos between 5% and 20% O 2 in NCSU23 medium [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The O2 concentration in the mammalian oviduct and uterus is about 5% [7], whereas in vitro cultured embryos are usually maintained under 5% CO2 and 95% air, which contains about 20% O 2 . Reduction of the O 2 concentration from 20% to 5% has been shown to enhance embryonic development in mice [8,9], sheep [10], cattle [11][12][13], and humans [14].…”
mentioning
confidence: 99%
“…Moreover, anaerobic bacteria are able to colonize the uterine lumen (15,16). Embryos are exceedingly sensitive to oxidative damage (17)(18)(19)(20)(21)(22)(23)(24), and blastocysts produced under low O 2 have significantly more inner cell mass cells than those produced under higher O 2 tensions (25). Accordingly, embryologists generally culture embryos under a low rather than high oxygen atmosphere (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%